Nanoparticles Perspective in Skin Tissue Engineering: Current Concepts and Future Outlook - Kaviani, Maryam; Geramizadeh, Bita (Current Stem Cell Research & Therapy, 2025)
Nanotechnology seems to provide solutions to the unresolved complications in skin tissue engineering. According to the broad function of nanoparticles, this review article is intended to build a perspective for future success in skin tissue engineering. In the present review, recent studies were reviewed, and essential benefits and challenging issues regarding the application of nanoparticles in skin tissue engineering were summarized. Previous studies indicated that nanoparticles can play essential roles in the improvement of engineered skin. Bio-inspired design of an engineered skin structure first needs to understand the native tissue and mimic that in laboratory conditions. Moreover, a fundamental comprehension of the nanoparticles and their related effects on the final structure can guide researchers in recruiting appropriate nanoparticles. Attention to essential details, including the designation of nanoparticle type according to the scaffold, how to prepare the nanoparticles, and what concentration to use, is critical for the application of nanoparticles to become a reality. In conclusion, nanoparticles were applied to promote scaffold characteristics and angiogenesis, improve cell behavior, provide antimicrobial conditions, and cell tracking.
Keywords: skin tissue engineering